1971
DOI: 10.1182/blood.v37.3.272.272
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Therapy and Combination Chemotherapy of Childhood Lymphocytic Leukemia

Abstract: In earlier combination chemotherapy regimens for childhood acute lymphocytic leukemia, nervous system leukemia terminated complete remission in over half the patients in a median time of 11 months. In the present study, cranial radiation (2400 R, 60Co) and intrathecal methotrexate given early in remission were added to combination chemotherapy in an attempt to prevent or delay central nervous system relapse and termination of complete remission. Of 35 consecutive children with previously untreated acute lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
7

Year Published

1971
1971
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(53 citation statements)
references
References 8 publications
1
45
0
7
Order By: Relevance
“…Dramatic alteration of leukemic mortality rate began alter 1948 with tlie first report OE an effective antimetabolite which produced selective toxicity against the tumor cells leading to temporary remission of the disease.5 'The discovery of other antimetabolites active ;against experimental leukemias of mice allowed the demonstration of the potential advantages of combination chemotherapy.l7 Furthermore, the critical importance of dose scheduling and dose levels was c:lemonstrated.lo Small (young) tumors were found more responsive to drug treatment than large (old) tumors which contained more cells potentially resistant to the drug, and which liad destroyed more of the animal's normal i:issues and impaired its functions, thus plating i t closer to deatli.lo In the last 20 years, we have been involved in extrapolating these fundamental principles 1 the basis for further therapeutic principles. T h e data represent tlie collaborative efforts of the Acute Leukemia Group B, an international organization active in clinical cancer research that we are privileged to serve as Chairman and Statistician, respectively, which has devoted substantial attention to acute lymphocytic leukemia.…”
mentioning
confidence: 99%
“…Dramatic alteration of leukemic mortality rate began alter 1948 with tlie first report OE an effective antimetabolite which produced selective toxicity against the tumor cells leading to temporary remission of the disease.5 'The discovery of other antimetabolites active ;against experimental leukemias of mice allowed the demonstration of the potential advantages of combination chemotherapy.l7 Furthermore, the critical importance of dose scheduling and dose levels was c:lemonstrated.lo Small (young) tumors were found more responsive to drug treatment than large (old) tumors which contained more cells potentially resistant to the drug, and which liad destroyed more of the animal's normal i:issues and impaired its functions, thus plating i t closer to deatli.lo In the last 20 years, we have been involved in extrapolating these fundamental principles 1 the basis for further therapeutic principles. T h e data represent tlie collaborative efforts of the Acute Leukemia Group B, an international organization active in clinical cancer research that we are privileged to serve as Chairman and Statistician, respectively, which has devoted substantial attention to acute lymphocytic leukemia.…”
mentioning
confidence: 99%
“…Sunderman & Pearson [18] found chemotherapy had no influence on the growth of these children. Aur et al [19], possibly because of more intensive therapy, found that for twenty-two of their thirty children increase in height was only 75% of the expected.…”
Section: Discussionmentioning
confidence: 94%
“…Fifty percent of the responders had previously failed induction with prednisone, while 83% of the nonresponders had previously failed prednisone induction. In acute adult myelogenous leukemia, (10)(11)(12)(13) many different schedules of Ara-C have been used, from rapid intravenous injections to 1,4,8,12,24,48, and 120 hr continuous infusions. There does not appear to be significant difference in the response rate to these schedules except that a larger amount of drug is necessary when Ara-C is given in the shorter time periods.…”
Section: Discussionmentioning
confidence: 99%